2009
DOI: 10.2147/ijn.s4931
|View full text |Cite
|
Sign up to set email alerts
|

Nanonized black soybean enhances immune response in senescence-accelerated mice

Abstract: Soy isofl avones may have applications in cancer prevention and anti-infl ammation, therefore this study was conducted to investigate the effect of dietary supplementation with black soybean on the immune response in the senescence-accelerated-prone mice (SAMP8) and -resistant mice (SAMPR1, as controls). The mechanism of isofl avones was also investigated. Six-month-old male SAMP8 and SAMR1 mice were divided into the control groups and experimental groups supplemented with nanonized (Nano-soy) or microparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…One of the mechanisms for lowering AFP level may have been the anti-inflammatory properties of soy. Previous studies have indicated that the isoflavones in soy may regulate the inflammatory response and immune function [ 64 , 65 ]. Moreover, genistein and secoisolariciresinol have anticancer properties on MCF-7 and BT20 in vitro [ 66 ] and have been suggested as the most potent inhibitors of cancer cell growth [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms for lowering AFP level may have been the anti-inflammatory properties of soy. Previous studies have indicated that the isoflavones in soy may regulate the inflammatory response and immune function [ 64 , 65 ]. Moreover, genistein and secoisolariciresinol have anticancer properties on MCF-7 and BT20 in vitro [ 66 ] and have been suggested as the most potent inhibitors of cancer cell growth [ 67 ].…”
Section: Discussionmentioning
confidence: 99%